2016
DOI: 10.1002/stem.2355
|View full text |Cite
|
Sign up to set email alerts
|

Kras is Required for Adult Hematopoiesis

Abstract: Previous studies indicate that Kras is dispensable for fetal liver hematopoiesis, but its rolein adult hematopoiesis remains unclear. Here, we generated a Kras conditional knockout allele to address this question. Deletion of Kras in adult bone marrow is mediated by Vav-Cre or inducible Mx1-Cre. We find that loss of Kras leads to greatly reduced TPO signaling in hematopoietic stem cells (HSCs) and multipotent progenitors (MPPs), while SCF-evoked ERK1/2 activation is not affected. The compromised TPO signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…We then generated compound Kras LSL G12D/1 ;Sos1 fl/fl ;Vav-Cre mice 10 (referred to as Kras;Sos1 2/2 mice thereafter) with Vav-Cre-mediated Kras G12D expression and Sos1 deletion. Unlike the Vav-iCre that drives oncogenic Kras expression in both fetal liver hematopoietic and endothelial cells, and thus leads to an embryonic lethality, 11 the Vav-Cre we used in our study 12,13 drove oncogenic Kras expression more strictly in the hematopoietic system after embryonic day 11.5, and thus approximately two-thirds of Kras LSL G12D/1 ;Vav-Cre (Kras) mice survived until adulthood (supplemental Table 1). As a consequence, approximately two-thirds of Kras;Sos1 2/2 mice also reached adulthood (supplemental Table 2).…”
Section: Sos1 Deletion Abolishes Oncogenic Kras-induced Hyperactivatimentioning
confidence: 99%
“…We then generated compound Kras LSL G12D/1 ;Sos1 fl/fl ;Vav-Cre mice 10 (referred to as Kras;Sos1 2/2 mice thereafter) with Vav-Cre-mediated Kras G12D expression and Sos1 deletion. Unlike the Vav-iCre that drives oncogenic Kras expression in both fetal liver hematopoietic and endothelial cells, and thus leads to an embryonic lethality, 11 the Vav-Cre we used in our study 12,13 drove oncogenic Kras expression more strictly in the hematopoietic system after embryonic day 11.5, and thus approximately two-thirds of Kras LSL G12D/1 ;Vav-Cre (Kras) mice survived until adulthood (supplemental Table 1). As a consequence, approximately two-thirds of Kras;Sos1 2/2 mice also reached adulthood (supplemental Table 2).…”
Section: Sos1 Deletion Abolishes Oncogenic Kras-induced Hyperactivatimentioning
confidence: 99%
“…9 We found that loss of Kras leads to greatly reduced TPO signaling in haematopoietic stem cells (HSCs), while SCF-evoked ERK1/2 activation is not affected. The compromised TPO signaling is associated with reduced long term-and intermediate-term HSC compartments and their reduced selfrenewal capability (Fig.…”
mentioning
confidence: 90%
“…All mouse lines were maintained in a pure C57BL/6 genetic background (>N10). Mice bearing a conditional oncogenic Nras allele (Nras Lox-stop-Lox (LSL) G12D/+ ) were crossed to Vav-Cre (Damnernsawad et al, 2016) mice to generate the experimental mice, including Nras LSL G12D/+ ; Vav-Cre, and Vav-Cre mice. These mice were genotyped as previously described Wang et al, 2011).…”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%